Strategy for Planting Pancasila Ideology in Countering Terrorism in State-Owned Enterprises - Budiono, Arief; Amin, Muryanto; Ridho, Hatta (Universitas Medan Area, 2025)
This study analyzes the strategy of planting the Pancasila ideology to prevent terrorism and radicalism in State-Owned Enterprises (SOEs). Terrorism in Indonesia is often triggered by the spread of a radical ideology that targets various sectors, including state-owned enterprises, through intolerance, education, and social media. Using qualitative descriptive methods, data were obtained through interviews, observations, and document analysis, then systematically analyzed using the Miles and Huberman technique. The study results show that the factors that cause radicalism in SOEs include low literacy of Pancasila, weak internal supervision, and the influence of social media. The strategy is to instill Pancasila values through socialization, training, and tolerance campaigns involving BNPT, community organizations, and religious leaders. The conclusion of the study emphasizes that a holistic approach based on the Pancasila ideology can prevent radicalism, provided that there is a strong synergy between the government, SOEs, and the community in the implementation of this strategy.